A Comparative Clinical Study to Evaluate the Efficacy of Yastimadhu Ghrita and Tila Kalka Madhu Ghrita in the Management of Sadhyo Vrana (AYUSHDHARA, 2025)
Sadhyo Vrana (acute wounds) is a common clinical condition that requires prompt and effective management to promote faster healing and prevent complications. Ayurveda offers various formulations for wound healing, among which Yastimadhu Ghrita and Tila Kalka Madhu Ghrita are known for their Vrana Ropana (wound-healing) properties. Objective: This study aims to compare the efficacy of Yastimadhu Ghrita and Tila Kalka Madhu Ghrita in the management of Sadhyo Vrana based on clinical parameters such as pain, inflammation, wound contraction, and epithelialization time. Methodology: A randomized comparative clinical trial was conducted on patients presenting with Sadhyo Vrana. Participants were divided into two groups: Group A received Yastimadhu Ghrita, and Group B received Tila Kalka Madhu Ghrita as local applications. The progress of wound healing was assessed using standard parameters, including pain reduction, exudate control, granulation tissue formation, and complete wound closure. Results: Both formulations showed significant improvement in wound healing. Yastimadhu Ghrita was more effective in reducing pain and inflammation due to its Shothahara (anti-inflammatory) and Vata-Pitta Shamaka properties. Tila Kalka Madhu Ghrita, with its Ropana and Vrana Shodhana (wound cleansing) effects, demonstrated faster granulation tissue formation and wound contraction. Conclusion: Both Yastimadhu Ghrita and Tila Kalka Madhu Ghrita are effective in the management of Sadhyo Vrana. However, Yastimadhu Ghrita is preferable for pain and inflammation, while Tila Kalka Madhu Ghrita promotes faster wound healing. Further studies with larger sample sizes are recommended.